Metabolomics of gingival crevicular fluid to identify biomarkers for periodontitis: A systematic review with meta‐analysis. (12th March 2021) - Baima, Giacomo; Corana, Matteo; Iaderosa, Giovanni; Romano, Federica; Citterio, Filippo; Meoni, Gaia; Tenori, Leonardo; Aimetti, Mario
Abstract: The present systematic review aimed to examine periodontitis‐specific biomarkers in the gingival crevicular fluid (GCF) that could have a diagnostic relevance, and to provide a qualitative assessment of the current literature. Metabolites are reliable indicators of pathophysiological statuses, and their quantification in the GCF can provide an outlook of the changes associated with periodontitis and have diagnostic value. Relevant studies identified from PubMed, Embase, Cochrane Library, and Scopus databases were examined to answer the following PECO question: "In systemically healthy individuals, can concentration of specific metabolites in the GCF be used to discriminate subjects with healthy periodontium (H) or gingivitis from patients with periodontitis (P) and which is the diagnostic accuracy?" Quality of included studies was rated using a modified version of the QUADOMICS tool. Meta‐analysis was conducted whenever possible. After the screening of 1, 554 titles, 15 studies were selected, with sample size ranging from 30 to 93 subjects. Eleven studies performed targeted metabolomics analysis and provided data for 10 metabolites. Among the most consistent markers, malondialdehyde levels were found higher in the P group compared with H group (SMD = 2.86; 95% CI: 1.64, 4.08). Also, a significant increase of 8‐hydroxy‐deoxyguanosine, 4‐hydroxynonenal, and neopterin was detected in periodontally diseased sites, while glutathione showed an inverse trend. When considering data from untargeted metabolomic analysis in four studies, more than 40 metabolites were found significantly discriminant, mainly related to amino acids and lipids degradation pathways. Notably, only one study reported measures of diagnostic accuracy. Several metabolites were differentially expressed in GCF of subjects across different periodontal conditions, having a major potential for investigating periodontal pathophysiology and for site‐specific diagnosis. Oxidative stress‐related molecules, such as malondialdehyde and 8‐hydroxy‐deoxyguanosine, were the most consistently associated to periodontitis (PROSPERO CRD42020188482).